Measuring opportunity: Redirecting education policy through research - Ryan H. Pfleger; Terri S. Wilson; Kevin G. Welner; Charles Bibilos (Arizona State University, 2018)
While scholars develop research with clear implications for policy and practice, this work has been largely ineffective in influencing thought beyond the academy. In this article, we explore challenges researchers face in designing public scholarship to influence policy. To illustrate, we profile one such effort, the "Opportunity to Learn Index," a national project designed to compare opportunities to learn in all 50 states, and we detail challenges related to method, analysis and presentation. This type of effort, we conclude, asks researchers to embrace unique challenges and the inescapably political nature of the knowledge enterprise, especially when engaging with non-researcher audiences.